Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Pupuk Organik pada CV Tani Sejahtera Utama - Ekalia Yusiana; I Ketut Manu Mahatmayana; Alisia Saputri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
CV Tani Sejahtera Utama is a company that has produced various kinds of organic fertilizers since 2021. CV Tani Sejahtera Utama is experiencing several problems, one of which is the number of emerging competitors that can reduce sales. This research aims to analyze the influence of the marketing mix on purchasing decisions and analyze marketing strategies to increase sales at CV Tani Sejahtera Utama. The method used is purposive sampling with a sample used for the first analysis of 60 respondents and the second analysis of 6 informants. This research data analysis uses multiple linear regression analysis and QSPM analysis. The results showed that the variables of product, price, place, promotion, people, process, and physical evidence simultaneously influenced purchasing decisions. Product, price, place, promotion, people, and process partially influence purchasing decisions, while place and physical evidence have no partial influence on purchasing decisions. Based on the results of the QSPM analysis, the alternative strategy is to improve company planning to increase sales volume with a TAS score of 7.33.